A Cu(II)‐Inorganic Co−Crystal as a Versatile Catalyst Towards 'Click' Chemistry for Synthesis of 1, 2, 3‐triazoles and β‐hydroxy‐1, 2, 3‐triazoles. Issue 1 (2nd January 2020) - Ghosh, Debasish; Dhibar, Subhendu; Dey, Amiya; Manna, Priyanka; Mahata, Partha; Dey, Biswajit
Abstract: A novel Cu(II) inorganic co‐crystal (CuICC ) i. e. [Cu(IMA)(2, 2′‐bipyridine)(H2 O)]2 ⋅ [Cu2 (IMA)2 (2, 2′‐bipyridine)2 ] ⋅ 6H2 O [where IMA=isopropylmalonic acid] has been synthesized. The inorganic co‐crystal of Cu(II) has been exploited as the versatile efficient catalyst for the cost effective facile synthetic approaches towards 'click' reaction which is effective for the several marked organic syntheses of 1, 2, 3‐triazoles and β‐hydroxy‐1, 2, 3‐triazoles. The catalytic process was performed through the single pot reaction based aerial synthetic protocol that does not need to perform any chromatographic purification technique. Interestingly, the CuICC acts as heterogeneous catalyst for the synthesis of 1, 2, 3‐triazoles, whereas its homogeneous catalytic role has been found for the synthesis of β‐hydroxy‐1, 2, 3‐triazoles. Abstract : Isopropylmalonic acid and 2, 2′‐bipyridine based water soluble Cu(II)‐inorganic co‐crystal acts as an efficient versatile catalyst for 'click' chemistry to synthesis 1, 2, 3‐triazoles and β‐hydroxy‐1, 2, 3‐triazoles at room temperature.